2009
DOI: 10.1016/j.juro.2009.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Suturing Technique and Urethral Plate Characteristics on Complication Rate Following Hypospadias Repair: A Prospective Randomized Study

Abstract: Suture technique has no influence on the outcome of tubularized incised plate urethroplasty. Urethral plate characteristics do not affect the complication rate except for plate width, which significantly affects the outcome. Adequate urethral plate width (8 mm or greater) is essential for successful tubularized incised plate repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 16 publications
7
56
0
7
Order By: Relevance
“…17 The presence of a narrow and shallow urethral plate has also been associated with an increased risk of complications, 18 although this finding has not been confirmed in sub sequent studies. 19,20 Moreover, the assessment of urethral plate characteristics seems to be somewhat subjective, with wide interobserver variability. 21 It is worth noting that some anatomical characteristics-such as the presence of a short penis, which is relatively common in patients with proximal hypospadias-can cause dissatisfaction in the absence of complications.…”
Section: Risk Factors For Failed Hypospadiasmentioning
confidence: 99%
“…17 The presence of a narrow and shallow urethral plate has also been associated with an increased risk of complications, 18 although this finding has not been confirmed in sub sequent studies. 19,20 Moreover, the assessment of urethral plate characteristics seems to be somewhat subjective, with wide interobserver variability. 21 It is worth noting that some anatomical characteristics-such as the presence of a short penis, which is relatively common in patients with proximal hypospadias-can cause dissatisfaction in the absence of complications.…”
Section: Risk Factors For Failed Hypospadiasmentioning
confidence: 99%
“…Literatürde sınırlı sayıda tek tek, devamlı, subkutiküler, tam kat sütürasyon teknikleri anlatılmaktadır (10). Bununla beraber, neoüretra aşamasında kullanılan sütür tekniğinin sonucu etkilemediğini bildiren araştırmalarda bulunmaktadır (9). Diğer yandan, subkütiküler ve tam kat sütür atılmasının cerrahi sonuçlarını değiştirmediğini bildiren çalışmalarda vardır (8).…”
Section: Discussionunclassified
“…A prospective randomized study showed no influence of suture technique on outcomes of tabularized incised plate urethroplasty [5]. Another Prospective study showed increased likelihood of post-operative complications with increase in GMS scoring [6].…”
Section: Discussionmentioning
confidence: 99%